Percepción del desarrollo de emprendimientos sostenibles y la imagen del destino Pedernales - Mazón Mendoza, Yulisa Alexandra (2022)
The objective of this research was to evaluate the perception of the development of sustainable entrepreneurships and their impact on the image of the Pedernales destination. A three-phase methodology was used: (1) a situational tourism diagnosis based on bibliographic searches, which highlights the practice of sun and beach tourism and infrastructure located mostly in urban areas, as well as the informality of enterprises and deficiency in basic services, tourist information and cooperation. (2) The elaboration of a market study through surveys, determined the profile of the visitor, which is an internal segment, coming from several Manabi cantons, they are young people who decide based on social networks and mainly consume lodging and restaurant services, they also have a traditional image of Pedernales, selecting conventional tourism activities, therefore, sustainable practices are little recognized. (3) Finally, an action plan was designed for the positioning of the image, which contains strategies for the public and private sector in areas like political/legal, cooperation, human capital, sustainability, public services/private infrastructure, tourism resources, innovation, image, promotion, communication/distribution and commercialization. In conclusion, despite the internal and external limitations, the territory is resilient and requires support to achieve optimal tourism development, because it has potential resources and enterprises willing to innovate and update, so the execution of the proposed strategic guidelines favors the sustainable management of establishments and influences the image of the destination, motivating the displacement of demand.